Exercise as a countermeasure for latent viral reactivation during long duration space flight. Issue 2 (3rd January 2020) - Agha, Nadia H.; Mehta, Satish K.; Rooney, Bridgette V.; Laughlin, Mitzi S.; Markofski, Melissa M.; Pierson, Duane L.; Katsanis, Emmanuel; Crucian, Brian E.; Simpson, Richard J.
Abstract: Latent viral reactivation is a commonly reported manifestation of immune system dysregulation during spaceflight. As physical fitness and exercise training have been shown to benefit multiple arms of the immune system, we hypothesized that higher levels of preflight physical fitness and/or maintaining fitness during a mission would protect astronauts from latent viral reactivation. Standardized tests of maximal strength, muscular endurance, flexibility, and cardiorespiratory fitness (CRF) were performed in 22 international space station (ISS) crewmembers before and after a ~6‐month mission. Reactivation of cytomegalovirus (CMV), Epstein‐Barr virus (EBV), and varicella zoster virus (VZV) was determined in crewmembers and ground‐based controls before, during, and after spaceflight. Crewmembers with higher CRF before spaceflight had a 29% reduced risk of latent viral reactivation compared to crew with lower CRF. Higher preflight upper body muscular endurance was associated with a 39% reduced risk of viral reactivation, a longer time to viral reactivation, and lower peak viral DNA concentrations, particularly for EBV and VZV. Latent viral reactivation rates were highest in crew with lower preflight CRF and higher levels of CRF deconditioning on return to Earth. We conclude that physical fitness may protect astronauts from latent viral reactivation during long duration spaceflight missions.